First results of Arar-magnetometer station in Saudi Arabia. Issue 5 (1st March 2020) - Alenazi, Moqbil S.; Mahrous, Ayman; Fathy, Ibrahim; Nouh, Mohamed; Elkholy, Essam; Elkhateeb, Magdy; Tharwat, Rasha; Shalaby, Heba; Ahmed, Yara
Abstract: This paper presents the first results of a new Arar-magnetometer station located (Geographic Coordinates: 30°50.2′N, 41°11.3′E) at Northern Border University in Saudi Arabia. The geomagnetic response detected by the station during a moderate magnetic storm of April 20, 2018 is examined as an initial study. The X-component of the magnetic field measured by the station showed a prompt increase coincident with the Sudden Storm Commencement (SSC) measured by the ACE satellite. The three components of the measured magnetic field were compared to the measured data from the nearest four INTERMAGNET stations as a test. The high rate of magnetic field digital data system of Arar-Magnetometer station with sampling rate of 0.1 s allowed us to study the geomagnetic pulsation at the northern region of the Arabian Peninsula for the first time, which will promote the research of space weather monitoring in that area.